“Earned Europeanness”: Turkey and Diaspora Turks in Europe (American Journal of Islam and Society, 2009)
Although the young and beautiful Europa was kidnapped by Zeus, the mostimportant hero of Greek mythology, she has given a general identity to thatcontinent which bears her name. Debates about the exact location of“Europe” and the definition of “Europeanness” have been going on for centuries.1 Europe has borne its complex identity as a continent until recenttimes; however, due to its surrounding regions and especially its culturopoliticaldefinitions, it does not have either geographically or culturallyexact boundaries. In fact, the positive meaning given in general to “Europe”and “Europeanness” in modern times has increased the number of countriesor population groups that wish to share this identity. But “otherness,” theunavoidable face of identity, has created an even more complex situationthat is now intertwined with this positive meaning.As distinct from “Westernism,” the concept of “Europeanness” hasdeveloped not only in terms of identity but also in terms of values, especiallyafter the Second World War.2 The performance shown in such issuesas the continuity of welfare and peace, stability, and democracy, as well asthe respect for human rights, cultural richness, and individual development,has had a great impact upon it.Although in the recent past Europe was a continentof horrible atrocity, intolerance, and war, it can be said that within thespace of fifty years, it has largely effaced this negativity and is actively tryingto be accepted as the symbol of “what is right and good.” ...